2020
DOI: 10.1155/2020/2965697
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms inTLR4Affect Susceptibility to Tuberculosis in Mexican Population from the State of Veracruz

Abstract: Tuberculosis is still a global public health problem, with an estimated 10 million new cases and 1.6 million deaths in 2017. Of all humans infected with M. tuberculosis, only 10-15% will develop active tuberculosis disease during their lifetime, and data suggest that along with environmental factors, genetic factors influence susceptibility to develop active disease. Toll-like receptors (TLRs) are pattern recognition receptors that play a central role in the initiation and shaping of adaptive immune responses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…influence the pathology and the immune responses against Mtb [37][38][39][40][41][42]. Indeed, single nucleotide polymorphisms may influence the differential SLAMF1 expression on neutrophils from TB patients and HD.…”
Section: R I P Tmentioning
confidence: 99%
“…influence the pathology and the immune responses against Mtb [37][38][39][40][41][42]. Indeed, single nucleotide polymorphisms may influence the differential SLAMF1 expression on neutrophils from TB patients and HD.…”
Section: R I P Tmentioning
confidence: 99%
“…To date, the results on the relationship between TLR gene polymorphisms and tuberculosis are not consistent, especially when they are performed in different populations. For example, Ortega et al found that the G allele of rs4986790 in TLR4 was associated with a reduced risk of tuberculosis in the Mexican population (Ortega et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is no significant correlation between IFNGR1 rs1327474 and the risk/protection of pulmonary tuberculosis (Naderi et al, 2015). The research results of the relationship between the rs4986790 gene polymorphism in TLR4 and tuberculosis are inconsistent in different populations (Ortega et al, 2020;Thada et al, 2013;Zhou & Zhang, 2020;L. Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…28 In a more recent study by Ortega et al, the minor allele G was also associated with deceased risk of active tuberculosis (OR 5 0.31). 29 A meta-analysis of genetic susceptibility studies showed an increased odds of parasitic infections associated with this SNP, but none of the studies included in the analysis involved Cryptosporidium or any other gastrointestinal parasite. 30 The TIRAP gene encodes an adaptor protein that is essential for downstream signaling of TLR2 and TLR4.…”
Section: Discussionmentioning
confidence: 99%